1981
DOI: 10.1007/bf01314835
|View full text |Cite
|
Sign up to set email alerts
|

Virus-like particles in bovine turbinate cells infected with bovine virus diarrhoea/mucosal disease virus

Abstract: Thin sections of bovine turbinate cells grown in culture and infected with the NADL strain of bovine virus diarrhoea/mucosal disease virus have been examined by electron microscopy. Infected cells exhibited ultrastructural modification of the rough endoplasmic reticulum and associated with this small numbers of virus-like particles were observed. Advanced stages of cytopathic effect were illustrated by cells showing a marked increase in electron-density. These features were not observed in uninfected control c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

1982
1982
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…TEM-based studies from the times in which the genus Pestivirus was still belonging to the family Togaviridae reported that pestivirus-infected cells exhibited ultrastructural modifications of rER and contained small numbers of virus-like particles (VLPs) [51,52]. Gray and Nettleton (1987) reported that Border Disease Virus (BDV)-infected cells contained several profiles of ER and many dense lamellar bodies, which when transversely sectioned appeared as multiple rows of tubules, 33 nm in diameter [52].…”
Section: Architecture and Properties Of The Replication Factories mentioning
confidence: 99%
“…TEM-based studies from the times in which the genus Pestivirus was still belonging to the family Togaviridae reported that pestivirus-infected cells exhibited ultrastructural modifications of rER and contained small numbers of virus-like particles (VLPs) [51,52]. Gray and Nettleton (1987) reported that Border Disease Virus (BDV)-infected cells contained several profiles of ER and many dense lamellar bodies, which when transversely sectioned appeared as multiple rows of tubules, 33 nm in diameter [52].…”
Section: Architecture and Properties Of The Replication Factories mentioning
confidence: 99%
“…Die Partikel von durchschnittlich 50 nm Durchmesser erscheinen als Cores mit allerdings wenig elektronendichtem Zentrum in der Zytoplasmamatrix, zuerst hauptsachlich der Golgi-Region, reifen durch Budding in intraplasmatische Zisternen hinein und sind spater zahlreich in Plasmavakuolen zu finden. Die reifen EA-Partikel differieren im Schnittbild von den fur BVD-und SP-Virus beschriebenen (4,13). Ein Budding an der Zellmembran haben die Autoren ebenfalls nicht nachweisen konqen.…”
Section: Ultrahistologiscbe Befunde Mit Dern Nichtcytopathogenen Stammunclassified
“…Ultrahistologische Studien an BVD-infizierten Kulturzellen unter ahnlicher Fragestellung liegen nur wenige vor (2,4,11). Sie wurden ausschliefllich an Modellen mit cytopathogenen BVD-Sthmen gewonnen.…”
Section: Introductionunclassified
“…Virus particles in electron micrographs appear as pleomorphic, mostly spherical, membrane-bound structures (Bielefeldt-Ohmann and Bloch, 1982). The viral core is an isometric, electron-dense structure, approximately 20 -30 nm in diameter (Horzinek et al, 1971; Chasey and Roeder, 1981;Gray and Nettleton, 1987). Surface projections cannot be distinguished on purified virus or virus particles in cells and tissues (Stott et al, 1974;Bielefeldt-Ohmann and Bloch, 1982).…”
Section: Physical-chemical Characteristicsmentioning
confidence: 99%
“…Viral replication takes place in the cell cytoplasm, closely associated with the endoplasmic reticulum. Budding of viral particles into cytoplasmic vesicles, endoplasmic reticulum modiHed into tubules (Chasey and Roeder, 1981;Gray and Nettleton, 1987), and autophagosomes or golgi networks (Bielefeldt-Ohmann et al, 1988) has been observed.…”
Section: Viral Growth Characteristicsmentioning
confidence: 99%